Sprinting technique: The key to increasing your speed - Coultman, L. (Track Coach, 2018)
Elements addressed in this article include, accelerative sprinting, maximum velocity sprinting, the breakdown of a sprint across 100m, ground contact time, movement mechanics, reactive forces, and perfecting the sprint start. The genetic makeup of an athlete may bless him or her with natural speed, but without working on proper sprinting mechanics an athlete will never reach full potential. This means speed can be taught and all athletes have the potential to increase their speed. Mastering proper sprint technique not only allows for an athlete to run faster but also reduces the risk of injury caused by poor mechanics. You could spend weeks working on top speed without seeing any improvement, whilst focused and attentive time spent on sprint form could potentially increase your speed within a few hours. For the sake of this article we will focus on horizontal sprinting across 100m. Obviously for other sprint events and team games there will be more detailed and more event/sport specific technical elements (bend running, multi-directional, stop-start movement etc.) but this article will provide a good basis of information that can be applied to some extent across all forms of sprinting.